2020
DOI: 10.36552/pjns.v24i2.443
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nursing Care Skills in Neonatal Unit: A Cross Sectional Observational Study

Abstract: Objective: Increased hospital treatment is required to reduce neonatal mortality in low/middle-income (LMIC) countries. Nurses are vital for providing safe and efficient treatment, but a shortage of nurses and high patient workloads can lead to missed treatment. We aimed to evaluate thecare provided to newborns and finding missing care using direct observation methods. Material and Methods:  Cross sectional observational study. The sample size was 133 which were calculated through Slovin’s formula. An ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Pre-intervention, all nurses participating in the study had a low mean and standard deviation of the attitude and practice of newly graduated nurses toward nursing care of preterm infants in the instructional guidelines and group discussion. Several studies have reported that preterm infant care is not fully respected by medical and nursing teams [ 26 , 27 ]. Nursing curricula may not adequately address caring for preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-intervention, all nurses participating in the study had a low mean and standard deviation of the attitude and practice of newly graduated nurses toward nursing care of preterm infants in the instructional guidelines and group discussion. Several studies have reported that preterm infant care is not fully respected by medical and nursing teams [ 26 , 27 ]. Nursing curricula may not adequately address caring for preterm infants.…”
Section: Discussionmentioning
confidence: 99%